Determinants of Financial Reports Quality in the Regional Government of Jayapura City - Siahay, Adolf Z. D.; Salle, Hesty T.; Afdal, Immanudin (AIBPM Publisher, 2023)
This research aims to determine the influence of human resource competence, internal control systems, and’’ the use of information technology on the quality of financial reports’’ on local government. This type of research is quantitative research with primary data and data collection techniques using questionnaires. The research was conducted at the Jayapura City Regional Apparatus Organization with a total of 98 respondents. Data analysis used in this research uses the Structural Equation Model (SEM) approach with the Partial Least Square method using’’ WrapPLS 8.0 Software. The research results show that the variables of human resource competence and internal control systems have a positive and significant effect on the quality of financial reports, while the variable use of information technology does not affect the quality of financial reports.